Applying Peer Review to Improve Students’ Descriptive Writing Text - Oktavianti, Devi; Pratiwi, Aisyah (English Education Department, 2023)
This research is conducted to determine whether there is a significant difference in students’ descriptive writing score after being treated using peer review compared to those students who did not get the same treatment. This is a quasi-experimental research design with one group as the experimental and one group as the control. Pre-test and post-test were also administered before and after the 10 times treatment given. The population of this research are all of the seventh-grade students in Bangka Islandy the total 80 students. Meanwhile, 50 students from two different classes were the sample of this research. The result of this research showed that the t-obtained in equal variances assumed 6.353 and the significant (2-tailed) was 0.00. Since t-obtained was higher than t-table (2.02) and the significant (2-tailed) was lower than computation with level significant (0.05), it could be stated that there was a significant difference in post-test between the experimental class and control class. It can be concluded that the using of peer review is able to improve the students’ descriptive writing score significantly.